2015
DOI: 10.1111/brv.12195
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence for source–sink populations: a review on occurrence, assessments and implications

Abstract: Assessing the role of local populations in a landscape context has become increasingly important in the fields of conservation biology and ecology. A growing number of studies attempt to determine the source-sink status of local populations. As the source-sink concept is commonly used for management decisions in nature conservation, accurate assessment approaches are crucial. Based on a systematic literature review of studies published between 2002 and 2013, we evaluated a priori predictions on methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 137 publications
2
84
0
Order By: Relevance
“…Echoing the findings of Furrer & Pasinelli [10], we also found notable taxonomic biases in study effort, with a predominance of studies on mammals in all climate zones, and birds in particular in temperate zones (Fig. S1).…”
Section: Results: Regional Biases In Source-sink Researchsupporting
confidence: 71%
See 3 more Smart Citations
“…Echoing the findings of Furrer & Pasinelli [10], we also found notable taxonomic biases in study effort, with a predominance of studies on mammals in all climate zones, and birds in particular in temperate zones (Fig. S1).…”
Section: Results: Regional Biases In Source-sink Researchsupporting
confidence: 71%
“…The review also revealed evidence of a taxonomic bias towards mammals and birds in source-sink research, and the authors suggested that sources and sinks may be more commonplace in nature than studies suggest [10]. Here, we perform a further review to examine whether there are regional biases in research on source-sink dynamics.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Methods have been developed to account for the issue of detectability, 55 based on the measure of the observer-animal distance (Distance Sampling; Buckland et al 2001) or on multiple surveys (hierarchical modeling, Royle and Dorazio 2008). Still, population size being the result of a balance between survival, recruitment, emigration and immigration, inferring population status from counts, whatever detectability is accounted for or not, may impair the assignment of the demographic status of a population (source vs. sink; 60 Furrer andPasinelli 2016, Weegman et al 2016). Surveys that consist of capturing, marking with permanent tags, releasing and then recapturing wild animals (i.e.…”
Section: Introduction 50mentioning
confidence: 99%